Perencanaan Pengendalian Kualitas untuk Meminimasi Terjadinya Defect pada Proses Produksi Kue Soes Menggunakan Metode Six Sigma - Chandrahadinata, Dody; Putri, Marsela (Institut Teknologi Garut, 2025)
PT. XYZ is a food company that is fully committed to the quality of its products. The company experienced a problem with the defect rate of soes products of 4.4% exceeding the maximum limit set by the company of 0.5%. So that efforts are needed to improve product quality and minimize the number of defective products. This study aims to identify in depth the main factors that cause the high level of product defects and formulate recommendations for improvement to significantly improve product quality. The method used is Six Sigma, which systematically identifies problems (define), measures performance (measure), analyzes root causes (analyze), implements improvements (improve), and controls changes (control). Based on the results of the study, it can be concluded that the defect of broken soes due to nozzle misalignment in the cream filling process is the dominant factor causing product defects. Based on the results of the root cause analysis, a number of recommendations for improvement have been formulated and implemented, which have succeeded in increasing the company's sigma level from 3.874 sigma to 4.082 sigma, thus meeting the set target.